FAKTOR YANG MEMPENGARUHI WIRAUSAHA WANITA MISKIN UNTUK MENCAPAI KEBERHASILAN USAHA - Munfaqiroh, Siti (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
Entrepreneurship is an individual who wants to create jobs in areas of education and expertise, have managers, and instituting his own business. Factors that encourage entrepreneurship someone to take career decisions can be known through personality assessment especially the experience and background. Therefore in entrepreneurship requires the ability or skill to be able in the face of stiff competition. In this study aims to (1) To determines what factors are motivating women's entrepreneurship (2) To determine any constraints faced by women in developing the business.